The Imaging Performance of Diagnostic Ultrasound Scanners Using the Edinburgh Pipe Phantom to Measure the Resolution Integral – 15 Years of Experience - Moran, Carmel M.; Inglis, Scott; McBride, Karne; Mcleod, Christopher; Pye, Stephen D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
The grayscale imaging performance of a total of 368 different scanner/transducer combinations from 39 scanner manufacturers measured over a period of 15 years is presented. Performance was measured using the resolution integral, a single figure-of-merit to quantify ultrasound imaging performance. The resolution integral was measured using the Edinburgh Pipe Phantom. Transducers included single element, linear, phased, curvilinear and multi-row arrays. Our results demonstrate that the resolution integral clearly differentiates between transducers with varying levels of performance. Two further parameters were also derived from the resolution integral: characteristic resolution and depth of field. We demonstrate that these two parameters can successfully characterize individual transducer performance and differentiate between transducers designed for different clinical and preclinical applications. In conclusion, the resolution integral is an effective metric to quantify and monitor grayscale imaging performance in clinical practice.
Keywords: education; training; quality assurance; physics and technology; resolution integral